Broker-based mechanism for cloud provider selection. (4th May 2020) - Achar, Raghavendra; Thilagam, P. Santhi; Acharya, Shreenath
Cloud computing has recently emerged as a new computing paradigm for delivering on demand virtualised computing resources over the internet on a pay-as-use basis. Applications hosted in cloud have different requirements which include both low level (resource) requirements and high level (performance) requirements. However, most of the cloud providers satisfy SLAs based on resource requirements rather than providing performance guarantees to applications. This gap creates a need for selecting a more suitable cloud provider who can satisfy performance requirements of applications along with resource requirements. This work aims at proposing a broker-based approach to rank cloud providers based on QoS requirements of customers. It helps the SaaS providers to save cost and complexity in choosing a suitable cloud provider for hosting applications. The experimental results show that proposed approach selects the suitable cloud provider for hosting various types of applications satisfying the needs of different cloud customers.